Radiobiology of Glioblastoma Recent Advances and Related Pathobiology - Pirtoli, Luigi; Gravina, Giovanni Luca; Giordano, Antonio (Current Clinical Pathology, 2016)
This text properly considers the most recent and relevant advances in molecular RB of GB, taking into account the related topics of pathobiology, and underscores the most promising translational perspectives from the preclinical to the clinical domain. Section I (From Bedside to Bench) discusses conditions associated with RT resistance of GB and the consequent RB hints, technology improvements intended to overcome RT-resistance of GB, mathematical modeling of RB parameters from clinical studies, the present impact of molecular prognostic factors in therapy of GB, and RT tolerance of normal brain. Section II (Preclinical Research and Pathobiology Topics) presents the traditional and mechanistic/molecular approaches to RB of GB, genetic and epigenetic studies on GB, issues of cell-death pathways, stem-like cells, invasiveness, tumor microenvironment, hypoxia, mi-RNA manipulations, and nanoparticle technology. Section III (Translational Perspectives) presents RB issues related to molecular profiling and classification of GB as frames of reference for clinical studies, translational perspectives of gene therapy, evolving protocols based on pre-clinical data and large data-bases and ontologic models. Radiobiology of Glioblastoma: Recent Advances and Related Pathobiology will be of great value to pathologists, medical oncologists, radiation oncologists as well as basic researchers and clinical investigators. .